Changes of the Fatty Acid Profile in Erythrocyte Membranes of Patients following 6-Month Dietary Intervention Aimed at the Regression of Nonalcoholic Fatty Liver Disease (NAFLD) - Dominika Maciejewska; Wojciech Marlicz; Karina Ryterska; Marcin Banaszczak; Dominika Jamioł-Milc; Ewa Stachowska (Canadian Journal of Gastroenterology and Hepatology)
Background. Nonalcoholic fatty liver disease (NAFLD) is closely related to the metabolism disorders of fatty acids. The pathogenesis of the disease includes an increased concentration of FFA in blood, an increase in the biosynthesis of fatty acids, and disorders in the process of β-oxidation. Objective. The aim of the study was to analyze the fatty acids in erythrocyte membranes among 55 patients with NAFLD who were subjected to a 6-month dietary intervention in order to reduce fatty liver. Materials and Methods. Basic anthropometric and biochemical measurements were performed. The profile of fatty acids was measured in the membranes of erythrocytes and analyzed by gas chromatography. The dietary compliance was evaluated using 72-diary questionnaires, anthropometric measurements. Results. With the reduction of fatty liver (p<0.01), the patients’ biochemical and anthropometric parameters were significantly improved. A significant decrease in the concentration of alanine aminotransferase (p<0.01) and asparagine aminotransferase (p<0.01) was observed, along with a decrease in the amount of insulin (p<0.05) and insulin resistance (p<0.05). Significant changes in terms of the fatty acid profile were observed among patients who followed the dietary intervention. There was a noticeable tendency in terms of the reduction palmitic acid (p<0.055) and a significant reduction of stearic acid (p<0.05). Significant changes in the profile of fatty acids were also associated with the reductionof palmitoleic (p<0.05) and oleic acids (p<0.05). Another statistically significant change observed was the increase in polyunsaturated fatty acids. In particular (p<0.01) the rise of eicosapentaenoic (p<0.055) and docosahexaenoic acids (p<0.55) was noted. Conclusion. The profile of fatty acids turned out to be a potential biomarker of the liver changes during NAFLD regression. Further research is needed to fully elucidate the usefulness and applicability of our findings in the management of NAFLD.